Impact of Drug-Eluting Stent Implantation for Femoropopliteal In-Stent Occlusion. (June 2016) - Tomoi, Yusuke; Soga, Yoshimitsu; Iida, Osamu; Shiraki, Tatsuya; Kobayashi, Yohei; Hiramori, Seiichi; Ando, Kenji
Purpose: To compare optimal balloon angioplasty with nitinol stenting and drug-eluting stent (DES) implantation for femoropopliteal in-stent occlusion (ISO).Methods: A dual center, retrospective study was performed from January 2004 to December 2014 encompassing 110 ISOs after bare nitinol stenting for a femoropopliteal lesion in 100 patients (mean age 72.7±10.1 years; 58 men). These patients underwent optimal balloon angioplasty with implantation of a bare stent (conventional group, n=79) or a DES (n=21). The primary endpoint was recurrent in-stent restenosis (Re-ISR); secondary endpoints were recurrent target lesion revascularization (Re-TLR), reocclusion, and major adverse limb events (MALE). Re-ISR or reocclusion was defined as ISR or occlusion after TLR. Restenosis was defined as a peak systolic velocity ratio >2.4 on a duplex scan or >50% stenosis on angiography. Univariate Cox regression analysis was used to identify any relationships between patient and procedure variables and the occurrence of Re-ISR; the results are presented as the hazard ratio (HR) and the 95% confidence interval (CI).Results: The mean follow-up period was 34.9±27.4 months. At 2 years, Kaplan-Meier estimated freedom from Re-ISR rates were 79.3% in the DES group and 20.2% in the conventional group, respectively (p<0.001). The rates of freedom from Re-TLR, reocclusion, and MALE at 2 years were 85.7%, 85.9%, and 85.7% in the DES group and 27.1%, 42.5%, and 25.3% in the conventional group, respectively (p<0.001, p=0.006, and p<0.001, respectively). Univariate analysis showed only postprocedure stenosis (HR 1.04, 95% CI 1.02 to 1.07, p<0.001) as a predictor of Re-ISR. Postprocedure ABI (HR 0.06, 95% CI 0.01 to 0.30, p<0.001) and DES use (HR 0.20, 95% CI 0.07 to 0.44, p<0.001) were associated with a lower likelihood of developing Re-ISR.Conclusion: In this small comparative study, DES stent implantation gives more favorable outcomes than conventional treatment for ISO after femoropopliteal stenting.